#gainingweightiscool: the use of transformation photos on Instagram among female weightlifters in recovery from eating disorders. Issue 1 (2nd January 2021) - Hockin-Boyers, Hester; Pope, Stacey; Jamie, Kimberly
ABSTRACT: In this article, we explore transformation photos on Instagram as 'digital artefacts' that can inform understandings of eating disorder recovery in the context of sport, exercise and health. Transformation photos are two images (from different time points) set alongside one another to represent the changing of bodies in look, shape or size. These images are prevalent within eating disorder recovery and fitness spaces on Instagram and typically display an individual's recovery journey through a before (thin) and after (more muscular) image comparison. By triangulating interview, photo elicitation and netnography data from research on female weightlifting as a tool for recovery from eating disorders, we explore transformation photos in relation to three intersecting themes; 1) new modes of 'becoming', 2) representation and 'mediated memories', and finally, 3) survivorship and identity. Our findings demonstrate that transformation photos are integral to the process and practice of recovery for women who use weightlifting as a tool for recovery from eating disorders. Moreover, we suggest that by engaging with a popular mimetic device (transformation photos), we were able to 'meet participants where they are' and offer a novel qualitative approach to understanding how digitally mediated lives are lived.